How Cells of the Immune System Prepare the Endometrium for Implantation - Teles, Ana; Zenclussen, Ana Claudia (Seminars in Reproductive Medicine, 2014)
Characterized by its cyclical regeneration and differentiation, the endometrium is one of the most dynamic tissues of the human body. As a main player during implantation and later development of the embryo it has a unique and extremely important role in the survival of species. This study is a review of the current literature focused on the cyclical restructuring of the endometrium and the morphological and cellular alterations during the different phases of the reproductive cycle. These changes confer specific receptive capabilities for implantation to take place. The mechanism of implantation is addressed as well as possible receptivity obstacles that can influence this process. More specifically, we discuss the involvement of immune cells in the establishment of implantation and its consequences for a successful pregnancy. A deep knowledge of the mechanisms involved in the regulation and transformation of the endometrium and embryo implantation is essential to understand disorders that can influence fertility and women health.
Keywords: endometrium; receptivity; implantation; infertility; immune cells